Effect of in Doping on the ZnO Powders Morphology and Microstructure Evolution of ZnO:In Ceramics as a Material for Scintillators - Muktupavela, Faina; Maniks, Janis; Grigorjeva, Larisa; Zabels, R.; Rodnyi, P.; Gorokhova, E. (Sciendo, 2018)
Transparent ZnO ceramics are of interest for use as material for high-efficiency fast scintillators. Doping ZnO ceramics in order to improve complex of their properties is a promising direction. In the present research, the role of indium in the ZnO nanopowders surface interactions and in the change of microstructures and photoluminescence (PL) characteristics of sintered cera-mics is considered. Undoped and 0.13 wt% In doped ZnO ceramics are obtained by hot pressing sintering. It has been found that indium leads to the transition of initially faceted ZnO particles to rounded, contributing to good sintering with formation of diffusion active grain boundaries (GBs). Unlike ZnO ceramics, ZnO:In ceramics microstructure is characterised by the trans-crystalline mode of fracture, faceted GBs with places of zig-zag forms and predominant distribution of In at the GBs. Such indium induced modifications of GBs promote removal of point defects and reduce PL parameter α = I def /I exc in comparison with the undoped ceramics. Results characterise ZnO:In cera-mics with improved GBs properties as a prospective material for scintillators.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; grain boundaries; hot pressing sintering; In doped ZnO ceramics; photoluminescence; ZnO powders